Genetic Variants in PTGS1 and NOS3 Genes Increase the Risk of Upper Gastrointestinal Bleeding: A Case–Control Study - Forgerini, Marcela; Urbano, Gustavo; Nadai, Tales Rubens de; Batah, Sabrina Setembre; Fabro, Alexandre Todorovic; Mastroianni, Patrícia de Carvalho (Frontiers in Pharmacology, 2021)
Objective: To assess the association between PTGS1 and NOS3 variant alleles and the risk to develop upper gastrointestinal bleeding secondary to complicated peptic disease (UGIB). Methods: A case-control study was conducted in a Brazilian complex hospital from July 2016 to March 2020. Case: patients with UGIB diagnosis. Control: patients admitted for surgery not related to gastrointestinal disorders. Variables: UGIB (outcome), genetic variants in PTGS1 and NOS3 genes (independent) and sex, age, schooling, ethnicity, previous history of gastrointestinal disorders, Helicobacter pylori serology, comorbidity, drug therapy, and lifestyle (confounding). The single nucleotide polymorphisms (SNPs) of PTSG1 gene (rs1330344, rs3842787, rs10306114, and rs5788) and NOS3 gene (rs2070744 and rs1799983) were determined using the real time polymerase chain reaction. Helicobacter pylori serology was determined through chemiluminescence technique. Logistic regression models were built and deviations of allelic frequencies from Hardy–Weinberg Equilibrium were verified. Results: 200 cases and 706 controls were recruited. Carriers of AG genotype of rs10306114 (OR: 2.55, CI95%: 1.13 – 5.76) and CA + AA genotypes of rs5788 (OR: 2.53, CI95%: 1.14 – 5.59) was associated with an increased risk for the UGIB development. In non-steroidal anti-inflammatory drugs (NSAIDs) users, the six variants evaluated modified the magnitude of the risk of UGIB; whereas in low-dose aspirin (LDA) users, an increased risk of UGIB was observed for four of them (rs1330344, rs10306114, rs2070744 and rs1799983). Personal ulcer history (p-value: < 0.001); Helicobacter pylori infection (p-value: < 0.011); NSAIDs, LDA and oral anticoagulant use (p-value: < 0.001); and alcohol intake (p-value: < 0.001) were also identified as independent risk factors for UGIB. Conclusion: This study presents two unprecedented analyzes within the scope of the UGIB (rs10306114 and rs2070744) and our findings showing an increased risk of UGIB in the presence of the genetic variants rs10306114 and rs5788, regardless drug exposure. Besides, the presence of the evaluated variants might modify the magnitude of the risk of UGIB in LDA/NSAIDs users. Therefore, our data suggest the need for a personalized therapy and drug use monitoring in order to promote patient safety.